Circannual rhythms in birds - Agarwal, Neha; Mishra, Ila (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2017)
Circannual rhythms are shown to mediate a wide range of seasonal and annual processes and help the animals to plan these events at most favourable time of the year. They are self sustained biological oscillations with a period close to 12 months and are entrained by both photic and non-photic cues. The understanding of the circannual rhythm would help us know the temporal adaptation in animals. The present review outlines the basics of circannual rhythms, its interaction with environmental factors, differences between the two mechanisms that regulate seasonal responses in organisms i.e. photoperiodism and circannual rhythm, and also present some experiments which have demonstrated circannual rhythm in reproduction, migration and molt behaviour of birds.